Isolation of a Leuconostoc mesenteroides Strain With Anti-Porcine Epidemic Diarrhea Virus Activities From Kefir Grains - Chang-Liao, Wan-Ping; Lee, An; Chiu, Yu-Han; Chang, Hui-Wen; Liu, Je-Ruei (Frontiers in Microbiology, 2020)
Swine grown under commercial conditions are vulnerable to environmental exposure to several viruses, which may cause infectious diseases and spread easily and rapidly, resulting in significant economic losses in animal husbandry. Previous studies have suggested that probiotics seem to be a new and promising alternative to vaccinations to protect animals against potential viral infections. In this study, we used the Vero cell culture model of infection to study porcine epidemic diarrhea virus (PEDV). We screened lactic acid bacteria (LAB) with anti-PEDV potential from kefir grains, which are starter cultures used to ferment milk into kefir. Twenty-nine LAB strains were isolated and identified as Enterococcus durans, Lactobacillus kefiri, Lactococcus lactis, and Leuconostoc mesenteroides, according to 16S rRNA and rpoA gene sequence analyses. The anti-PEDV activities of the LAB intracellular extracts were compared, and the intracellular extracts of Ln. mesenteroides showed higher anti-PEDV activities than that of the other species. Among the Ln. mesenteroides strains, a strain designated YPK30 showed a higher growth rate than that of the other strains and was further evaluated for its anti-PEDV activity. The results showed that the intracellular extracts of Ln. mesenteroides YPK30 possessed in vitro prophylactic, therapeutic, and direct-inhibitory effects against PEDV in the Vero cell model. The expression levels of type 1 interferon (IFN)-dependent genes, including Myxovirus resistance 1 (MX1) and interferon-stimulated gene 15 (ISG15) were significantly increased after treatment with intracellular extracts of Ln. mesenteroides YPK30 for 24 h. Such expression suggests that the anti-PEDV activity of Ln. mesenteroides YPK30 could be attributed to its up-regulatory effect on the expression of MX1 and ISG15 genes. These results suggested that Ln. mesenteroides YPK30 has the potential to provide some levels of host protection against PEDV infections.